Analisis Employee Engagement, Komitmen Organisasi, Rotasi Pekerjaan dan Kompensasi terhadap Kinerja Karyawan pada PT. Asuransi Jasindo Syariah - Nasa Al Akbar; Gendut Sukarno (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Employee performance is the result or performance of employees who are assessed in terms of quality and commitment based on work standards set by the company. This study aims to determine the effect of Employee Engagement, Organizational Commitment, Job Rotation and Compensation on Employee Performance. It is expected to make considerations for decision makers in the company. The population in this study is employees PT Asuransi Jasindo Syariah as many as 39 people, with the sampling method is the Census or Saturated method. The data analysis technique in this study uses Partial Least Square (PLS). From the results of data analysis it can be concluded that: 1) employee engagement has a positive and significant effect on employee performance, 2) organizational commitment has a positive and significant effect on employee performance, 3) job rotation has a negative and insignificant effect on employee performance, and 4) compensation has an effect positive and significant impact on employee performance. Keywords: Employee Engagement, Organizational Commitment, Job Rotation, Compensation, Employee Performance